Cost-effectiveness of a diabetes group education program delivered by health promoters with a guiding style in underserved communities in Cape Town, South Africa. Issue 5 (May 2015) - Mash, Robert; Kroukamp, Roland; Gaziano, Tom; Levitt, Naomi
Highlights We evaluate cost-effectiveness of group diabetes patient education. Education is by mid-level health workers in a middle income African country. Group diabetes education was effective in lowering blood pressure at 1-year. The incremental cost-effectiveness ratio was 1862 $/QALY. Group diabetes education is a cost-effective intervention in this context.